Rethinking Islamic politics in Tunisia: a Gramscian analysis - Merone, Fabio (Critical studies on Islamism series, 2025)
"Written by two renowned experts of political Islam, this book uses the philosophy of Gramsci to provide a new perspective on Islamism and Salafism in Tunisia. In particular, the book explains how the ideological/theological side of Islamic activism realizes itself into practical political action. In doing so, it argues that Islamists and Salafists can be described as 'post-Islamist' in the same way communist parties became 'post-communist' and 'post-ideological', where ideology has the same meaning as revolutionary politics. The theoretical approach and critical outlook developed here provides an innovative framework to understand Islamist politics in other contexts"-- Provided by publisher